- #1

- 39

- 1

the exersice is from stewart's book Ch 5.4 #3

i have the function [tex] y = \frac{x}{a^2 \sqrt(a^2-x^2)} [/tex]

this can be simplified like this

[tex] y = c*R(x) [/tex]

where R(x) = P(x)/Q(x) my question is

in the step of -P(x)*Q'(x) why is not zero?

if the formula says [tex] U^n = nU^n ^(-1) du [/tex]

in the exaple would be [tex] U^n = nU^n ^(-1) du [/tex]

(everything)*(2a*0+2x*1) so that zero makes all zero!

so our answer is [tex] y' = \frac{1}{a^2 \sqrt(a^2-x^2)} [/tex], doesn't it?

i saw the real answer and its [tex] y' = \frac{1}{\sqrt((a^2-x^2))^3} [/tex]

im i wrong in the formula that i use for [tex] U^n [/tex]

i have the function [tex] y = \frac{x}{a^2 \sqrt(a^2-x^2)} [/tex]

this can be simplified like this

[tex] y = c*R(x) [/tex]

where R(x) = P(x)/Q(x) my question is

in the step of -P(x)*Q'(x) why is not zero?

if the formula says [tex] U^n = nU^n ^(-1) du [/tex]

in the exaple would be [tex] U^n = nU^n ^(-1) du [/tex]

(everything)*(2a*0+2x*1) so that zero makes all zero!

so our answer is [tex] y' = \frac{1}{a^2 \sqrt(a^2-x^2)} [/tex], doesn't it?

i saw the real answer and its [tex] y' = \frac{1}{\sqrt((a^2-x^2))^3} [/tex]

im i wrong in the formula that i use for [tex] U^n [/tex]

Last edited: